Recurrent Left Pleural Effusion Following Left Atrial Appendage Closure With the Watchman Device - Halaby, Rim (JACC Case Rep, 2020)
A 75-year-old woman with recent left atrial appendage closure with the Watchman device (Boston Scientific, Natick, Massachusetts) presented with recurrent left pleural effusion. The constellation of chest pain, pericardial effusion, and exudative pleural effusion were suggestive of an inflammatory process precipitated by microperforation of the fixation anchors during the Watchman placement. (Level of Difficulty: Intermediate.)